A city in ruins or a living city: spatial and temporal presence and visual refutation in representations of Detroit. (22nd October 2020) - Yang, Michelle Murray
Abstract: How can rhetors refute dehumanizing rhetoric regarding cities? To address this question, I analyze the argumentative clash between two photobooks: Yves Marchand and Romain Meffre's The Ruins of Detroit and Dave Jordano's Detroit Unbroken Down . I focus on strategies they use to create spatial and temporal presence in order to argue for how viewers ought to see Detroit. I find that Marchand and Meffre use the frame of abandonment and adhere to conventions of contemporary de-industrial ruin photography to argue that Detroit is an abandoned ruinscape. They relegate Detroit to the past and make Detroiters absent, thereby distancing viewers from the city's residents. I find that Jordano refutes that view of Detroit by using the humanity frame and elements of portraiture photography to argue that Detroit is a living city. He situates the city in the present and makes Detroiters present, thereby highlighting residents' agency and encouraging connection between viewers and residents. The analysis shows how visual arguments can make present the humanity of cities and their residents, thereby making it increasingly difficult to perpetuate dehumanizing discourse regarding cities.